(3CYeGd GdbdhH Hjf GdeJcdejf hGdUhajI hehba Cgd GdSfI efge (B/s - (3GdYGRej, eWQ SGde Hf MejOs; (3GdLdjfO, eMeO GdSjOs 1940- ((3GdchjJ (B:s (3ecJHI Cgd GdCKQ ddfTQ hGdJhRjY ,s, 2014)
(3Ef GdCYeGd GdbdHjI (B: (3gj Cge CfhGY GdCYeGd, dCf YdjgG eOGQ SGFQ GdCYeGd, aHOhfgG dG JfaY Jdc GdCYeGd, hCYeGd GdbdhH JTed GdCehQ GdGYJbGOjI hGdYedjI, EP GdbdhH dgG CYeGd ceG Cf GSGFQ GdLhGQM CYeGdG, h bO JTJQc GdbdhH eY GdLhGQM aj Jdc GdCYeGd hbO JfaQO HgG(B. (3hCYeGd GdbdhH cKjQI heJYOOI, hbO JWQbJ ai gPg GdQSGdI Edi feGPL ef CYeGd GdbdhH GdeMVI(B.s
(3HHdjhLQGajI (B: (3UaMI (B325-360.s
Keywords: (3GdaQb GdESdGejIs; (3adSaI ESdGejIs; (3Cgd GdSfIs; (3GdJUhas; (3GdeJcdejfs; (3Yde GdcdGes; (3YbjOIs